Locust Attack: Managing and Control Strategies by the Government of Pakistan: A review on Locust Attack in Pakistan - Muhammad Usman; Muhammad Ijaz; Mariam Aziz; Muhammad Hassan; Ahmed, Agha Mushtaque; Din Muhammad Soomro; Saif Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
During outbreaks of Schistocerca gregaria, the desert locust swarms, and plagues known to infest numerous regions across wide areas of Asia and Africa. The locust devours large amounts of crops and rangeland flora. Recently the locust outbreak began in June 2018 in Saudi Arabia’s distant areas and entered in Pakistan March 2019, destroying main crops such as cotton, wheat, rice and maize in many districts across Baluchistan, Punjab, Sindh and Khyber Pakhtunkhwa provinces. On February 1, 2020, a national emergency was proclaimed, and the Plant Protection department countered by launching monitoring and prevention activities with the help of other institutions in Pakistan, as well as global and bilateral organizations. Surveillance and control activities were carried out with the majority of the insecticide formulations being oil-based ultra-low volume, nonconventional and green technology approaches. In addition, the Pakistani government devised a comprehensive phase wised management strategy as well as a National Locust Control Center with fast retort troops deployed in critical areas. Additional surveillance and control measures are needed to stop or alleviate desert locust-related agriculture damages. The unusual characteristics of the desert locust, as well as the size and frequency of swarming events, make developing and implementing IPM measures difficult. The state of prospective integrated measures to control locusts is discussed, as well as proactive and preventive intervention options.